PERSEPSI MAHASISWA TERHADAP PERKULIAHAN FIQH LUGHAH MELALUI GOOGLE CLASSROOM - Albantani, Azkia Muharom; Mubarak, Mahfuz Rizqi; Rozak, Abd.; Ardiansyah, Ade Arip (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2021)
The Covid-19 pandemic to date has caused learning to be carried out remotely to prevent further transmission of the virus. The use of Google Classroom is a solution for learning fiqh lughah online at this critical time. So far, there are still few studies that examine student perceptions of online learning of fiqh lughah. Therefore, this study aims to investigate student perceptions of online learning of fiqh lughah using Google Classroom. This research is exploratory, investigative research with 33 students as the subject. All exploratory data were analyzed using descriptive statistical techniques by adopting several steps: tabulating the Microsoft Excel application data, adding a percentage score to the data, and presenting the analyzed data in a summary table. These findings reveal that distance learning using Google Classroom gets a positive response from students even though they have to adapt more intensely to be comfortable with the learning process. Therefore, learning fiqh lughah through Google Classroom should be considered as an alternative media for online learning.